2011
DOI: 10.5194/acp-11-11707-2011
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for non-linear chemistry of ship plumes in the GEOS-Chem global chemistry transport model

Abstract: Abstract. We present a computationally efficient approach to account for the non-linear chemistry occurring during the dispersion of ship exhaust plumes in a global 3-D model of atmospheric chemistry (GEOS-Chem). We use a plume-ingrid formulation where ship emissions age chemically for 5 h before being released in the global model grid. Besides reducing the original ship NO x emissions in GEOS-Chem, our approach also releases the secondary compounds ozone and HNO 3 , produced during the 5 h after the original … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 29 publications
7
125
4
Order By: Relevance
“…Model calculations with a parameterization of the ship plumes suggest that with this approach we overestimate NO x concentrations and ozone formation (Huszar et al, 2010;Vinken et al, 2011). Our results may not be directly comparable as we use a much finer horizontal model resolution.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Model calculations with a parameterization of the ship plumes suggest that with this approach we overestimate NO x concentrations and ozone formation (Huszar et al, 2010;Vinken et al, 2011). Our results may not be directly comparable as we use a much finer horizontal model resolution.…”
Section: Discussionmentioning
confidence: 42%
“…Our results may not be directly comparable as we use a much finer horizontal model resolution. In addition Vinken et al (2011) find that the differences between the plume calculations and instant dilution are smallest over strongly polluted seas such as the North Sea. This suggests that implementing a parameterization of the ship plumes would not change our results significantly.…”
Section: Discussionmentioning
confidence: 95%
“…Liang and Jacobson (2000) showed that premature mixing of urban and background air masses can lead to either overestimates or underestimates of OPE. Model simulations of ship plumes indicate particularly large ozone overestimates when mixing NO x from the plumes into otherwise clean grid cells (Davis et al, 2001;Vinken et al, 2011). On a global scale, Wild and Prather (2006) found from an asymptotic error convergence method that grid averaging in a 2.8 • × 2.8 • model caused a +4 % bias in the global tropospheric ozone burden, with larger errors on regional scales.…”
Section: Introductionmentioning
confidence: 99%
“…Model simulations of ship plumes indicate particularly large ozone overestimates when mixing NO x from the plumes into otherwise clean grid cells (Davis et al, 2001;Vinken et al, 2011). On a global scale, Wild and Prather (2006) found from an asymptotic error convergence method that grid averaging in a 2.8 • × 2.8 • model caused a +4 % bias in the global tropospheric ozone burden, with larger errors on regional scales. Ito et al (2009) compared global models of varying resolutions and concluded that artificial mixing of biogenic VOC emissions into coarse grid cells drives excessive conversion of NO x to organic nitrate reservoirs, leading to release of NO x downwind under higher OPE conditions and thereby causing excessive ozone production.…”
Section: Introductionmentioning
confidence: 99%
“…[109] Alternative attempts to address this have included a box model approach, [110] a large eddy model approach [116] and a ship plume parameterisation in a regional model. [117] A promising approach is the 'plume-in-grid' formulation by Vinken et al, [118] which, when incorporated in a global model, showed that ignoring these effects leads to overestimation of NO x and O 3 concentrations in the North Atlantic by 50 and 10-25 % respectively. Further work is clearly required to determine how grid-scale ship plumes can be parameterised in numerical models.…”
Section: Atmospheric Nutrient Supply To the Surface Oceanmentioning
confidence: 99%